Blending Tradition and Innovation: Student Opinions on Modern Anatomy Education - Alina Maria Șișu; Emil Robert Stoicescu; Sorin Lucian Bolintineanu; Alexandra Corina Faur; Roxana Iacob; Delius Mario Ghenciu; Alexandra-Ioana Dănilă; Ovidiu Alin Hațegan (Education Sciences)
Anatomy education has evolved significantly with the introduction of diverse instructional techniques. This review evaluates these methods, including traditional cadaver dissection, three-dimensional (3D) model printing, virtual dissection using tools like the Anatomage table, problem-based learning (PBL), and the use of wax and plastinated models. Each approach presents unique benefits and challenges. Cadaver dissection remains invaluable for providing hands-on experience and a deep understanding of anatomical structures, although it faces ethical, logistical, and financial constraints. Wax and plastinated models offer durable, precise representations of anatomical structures without the ethical concerns associated with cadavers. Additionally, 3D printing and virtual dissection have emerged as effective supplementary tools, enhancing spatial understanding and allowing repeated practice. PBL integrates anatomical knowledge with clinical reasoning, promoting critical thinking and problem-solving skills. The main aim of this study was to gather and analyze students’ opinions on various anatomy teaching methods, while a secondary objective was to review the literature on novel and traditional approaches in anatomy education. This review emphasizes the importance of incorporating a variety of teaching methods to create a dynamic and engaging anatomy curriculum, preparing students for clinical practice.